A study on the application of strategic management to the contractor’s firm / Norsyakila Shahrudin - Shahrudin, Norsyakila (2006)
The slowdown in the construction industry in Malaysia can be improved by continuous search for construction innovation and excellence through research, development, training and management. There are three main problems which are happened in the construction industry in Malaysia. Nowadays, many contractors involved in construction industry in Malaysia. This phenomenon is the main reason which contributes to high competitive in Malaysia. Market size in domestic industry is small and gives the limited job opportunities. So, the contractors must be skilful, expert and professional to go through into international market. Besides that, the contractors competitive still at the lower level. Domination of the foreign contractors in the market industry is more increase and job opportunity to local contractors become less. The percentage of contractors who are applying the SWOT Analysis in the organization will be defined from this study. The scope is limited among contractors around Seberang Perai Tengah which randomly selected. The data and information for this study will be obtained by questionnaire. SWOT Analysis is the main factor in strategic management that can contribute to the successful of the organization in developing the strong company in domestic market. Strategic management is one of the solutions which can help to increase the growth of construction industry in Malaysia which is towards to global successfully.